Healing the Fundamental Unit of Heredity (Gene Therapy): Current Perspective and What the Future Holds - Bunga Anggreini Sari; Azalia Talitha Zahra; Ganda Purba Tasti; Ziske Maritska (Molecular and Cellular Biomedical Sciences, 2021)
The ability to make precise adjustments to the human genome has been a goal of healing in which gene also introduces as the fundamental unit of heredity, in biomolecular technology in genetic diseases have opened new knowledge such as gene therapy. Gene therapy is a technique to repair DNA where its usage is to treat the malignancy and inherited genetic diseases. Gene therapy is a choice to the genetic cloth that goals to remedy a sickness this is hard to deal with or perhaps has no treatment. Currently, gene remedy is done in approaches to patients, specifically embryonic cells and somatic cells, every in vivo and ex vivo. Moral considerations with modification of the difficulty's cells and oversight of regulation and reagents want to be taken into consideration within the gene therapy project. Applications for using gene remedies have begun to be widely used, which include in case of maximum cancers, coronary heart disorder, infectious sicknesses, and others. Gene therapy has spread to a wide range of applications then go beyond the modification of genetic disorders. Advances in genetic modification of cancer cells and immunity and the use of viruses and bacteria to control cancer cells have resulted in many clinical trials and product developments for cancer treatment. The miracles and blessings of gene therapy are might believe, but even though they are being studied and developed now and, in the future, so that the desire for gene therapy may be even better future.Keywords: gene therapy, genetic recombination, gene therapy application